SUPERVISI DIGITAL OLEH KEPALA SEKOLAH: STRATEGI MENINGKATKAN KUALITAS PEMBELAJARAN BERBASIS TEKNOLOGI DI SMA NEGERI 2 BANDAR LAMPUNG - Reski Gunawan; Rochmat Widodo; Subandi Subandi; Oki Dermawan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Objective: This study aims to analyze the implementation of digital supervision conducted by the principal in improving the quality of technology-based learning at SMA Negeri 2 Bandar Lampung. The research employed a qualitative approach with a case study design, using observation, in-depth interviews, and digital documentation as data collection techniques. The findings indicate that digital supervision is implemented through the use of a Learning Management System (LMS), Google Drive, QR code–based digital attendance, and video-based classroom observations. Digital supervision has been proven to enhance teacher discipline, the quality of instructional materials, learning effectiveness, and teachers’ technological competence. In addition, a stronger culture of pedagogical reflection has emerged, as teachers are able to review their teaching practices through recorded learning videos. However, the implementation of digital supervision still faces several challenges, including variations in teachers’ ICT skills, internet connectivity issues, resistance to change, and the limited time of the principal. Overall, digital supervision serves as an effective strategy for improving learning quality and teacher professionalism in the era of technology-based education.